The Fantasy Engagement Scale: A Flexible Measure of Positive and Negative Fantasy Engagement. Issue 3 (4th May 2017) - Plante, Courtney N.; Reysen, Stephen; Groves, Christopher L.; Roberts, Sharon E.; Gerbasi, Kathleen
ABSTRACT: Despite the prevalence of fantasy activities in day-to-day life, there has been little systematic psychological research on fantasy. Existing work is scattered across numerous fantasy-related topics and are rarely viewed as a collective body of work. We propose a scale of fantasy engagement that addresses this scattered and often-contradictory literature by assessing both positive and negative aspects of fantasy engagement. Across four studies we develop and validate the Fantasy Engagement Scale, establishing its reliability, validity, and applicability to topics including well-being, escapism, and mental imagery. The results begin to reconcile contradictions in the existing research and have implications for future work on fantasy specifically and for studies of fantasy-related activities.